Construction of an AI-2 quorum sensing induced heterologous protein expression system in Escherichia coli - Shang, Fei; Wang, Hui; Zhang, Dan; Wang, Wenhui; Yu, Jiangliu; Xue, Ting (PeerJ, 2021)
Background The pET expression system based on T7 promoter which is induced by isopropyl-β-D-1-thiogalactopyranoside (IPTG) is by far the most commonly used system for production of heterogeneous proteins in Escherichia coli. However, this system was limited by obvious drawbacks including the host toxicity and metabolic burden imposed by the presence of IPTG. Methods In this study, we incorporated the autoinducer-2 (AI-2) quorum sensing system to realize autoinduction of the pET expression system. The autoinduction expression vector pXWZ1 was constructed by inserting the lsr promoter regions into the pET28a(+) vector. The expression efficiency of the reporter genes gfpuv and lacZ by the pXWZ1 and pET28a(+) vectors were compared. Results The results showed that the expression levels of the both report genes in the cells transformed with pXWZ1 without any addition of exogenous inducer were higher than that transformed with pET28a(+) vectors by the induction of IPTG. Conclusion This new auto-induction system will exclude the limitations of the IPTG induction including toxic to host and increasing formation of inclusion body and will become a more economical and convenient tool for recombinant protein expression.
Keywords: AI-2 quorum sensing; Protein expression; Auto-induction; Escherichia coli